Pre-clinical evaluation of a nanoparticle-based blood-pool contrast agent for MR imaging of the placenta. (September 2017) - Ghaghada, Ketan B.; Starosolski, Zbigniew A.; Bhayana, Saakshi; Stupin, Igor; Patel, Chandreshkumar V.; Bhavane, Rohan C.; Gao, Haijun; Bednov, Andrey; Yallampalli, Chandrasekhar; Belfort, Michael; George, Verghese; Annapragada, Ananth V.
Abstract: Introduction: Non-invasive 3D imaging that enables clear visualization of placental margins is of interest in the accurate diagnosis of placental pathologies. This study investigated if contrast-enhanced MRI performed using a liposomal gadolinium blood-pool contrast agent (liposomal-Gd) enables clear visualization of the placental margins and the placental-myometrial interface (retroplacental space). Non-contrast MRI and contrast-enhanced MRI using a clinically approved conventional contrast agent were used as comparators. Materials and methods: Studies were performed in pregnant rats under an approved protocol. MRI was performed at 1T using a permanent magnet small animal scanner. Pre-contrast and post-liposomal-Gd contrast images were acquired using T1-weighted and T2-weighted sequences. Dynamic Contrast enhanced MRI (DCE-MRI) was performed using gadoterate meglumine (Gd-DOTA, Dotarem ® ). Visualization of the retroplacental clear space, a marker of normal placentation, was judged by a trained radiologist. Signal-to-noise (SNR) and contrast-to-noise (CNR) ratios were calculated for both single and averaged acquisitions. Images were reviewed by a radiologist and scored for the visualization of placental features. Contrast-enhanced CT (CE-CT) imaging using a liposomal CT agent was performed for confirmation of the MR findings. Transplacental transport of liposomal-Gd was evaluated by post-mortem elemental analysis of tissues. Ex-vivo studies in perfused human placentae from normal, GDM, and IUGR pregnancies evaluated the transport of liposomal agent across the human placental barrier. Results: Post-contrast T1w images acquired with liposomal-Gd demonstrated significantly higher SNR (p = 0.0002) in the placenta compared to pre-contrast images (28.0 ± 4.7 vs. 6.9 ± 1.8). No significant differences (p = 0.39) were noted between SNR in pre-contrast and post-contrast liposomal-Gd images of the amniotic fluid, indicating absence of transplacental passage of the agent. The placental margins were significantly (p < 0.001) better visualized on post-contrast liposomal-Gd images. DCE-MRI with the conventional Gd agent demonstrated retrograde opacification of the placenta from fetal edge to the myometrium, consistent with the anatomy of the rat placenta. However, no consistent and reproducible visualization of the retroplacental space was demonstrated on the conventional Gd-enhanced images. The retroplacental space was only visualized on post-contrast T1w images acquired using the liposomal agent (SNR = 15.5 ± 3.4) as a sharply defined, hypo-enhanced interface. The retroplacental space was also visible as a similar hypo-enhancing interface on CE-CT images acquired using a liposomal CT contrast agent. Tissue analysis demonstrated undetectably low transplacental permeation of liposomal-Gd, and was confirmed by lack of permeation through a perfused human placental model. Conclusions: Contrast-enhanced T1w-MRI performed using liposomal-Gd enabled clear visualization of placental margins and delineation of the retroplacental space from the rest of the placenta; the space is undetectable on non-contrast imaging and on post-contrast T1w images acquired using a conventional, clinically approved Gd chelate contrast agent. Graphical abstract: Highlights: Clear visualization of placental margins is critical for accurate diagnosis of pathologies. Liposomal-Gd is a long circulating blood-pool contrast agent for use in MRI. Liposomal-Gd enables clear visualization of placental margins and placental-uterine interface on MRI. Liposomal-Gd exhibits undetectably low trans -placental permeation. Liposomal-Gd may be useful for evaluation of placental pathologies, especially invasive placentation.